Pendidikan Perlindungan Konsumen Kepada Masyarakat Desa Di Kecamatan Teon Nila Serua Kabupaten Maluku Tengah - Sarah Selfina Kuahaty; Teng Berlianty; Theresia Louize Pesulima; Agustina Balik; Maichel Lesnussa (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Lack of public understanding of civil rights owned, bringing its legal problems for the community. This is the basis of consideration of the Civil Law Section of the Faculty of Law, Pattimura University to conduct community service activities as a form of implementation of the Tri Dharma of universities, one of the legal topics presented is related to consumer protection issues.Purposes of Devotion: Providing an understanding of consumer protection law of the community, especially the community in 3 (three) villages in Teon Nila Serua sub-district, namely Layeni village, Wotay village, and Lesluru village. Method of Devotion: Method of Dedication is using legal counselling to the community in 3 (three) villages in Teon Nila Serua district of central Maluku Regency.Results of the Devotion: In the implementation of these activities, it is known that many consumer problems such as buying goods that have been offered, goods that have defects, or sometimes goods that have been damaged, such as rice or sugar but purchased because they are deceived by low prices, which turns out to be detrimental to society. As consumers, the public does not know that they can raise objections and demand their rights back. Providing legal education, especially consumer protection, can make society an intelligent consumer.